2011
DOI: 10.1108/20426781111146745
|View full text |Cite
|
Sign up to set email alerts
|

Strategic marketing's contribution to Australasian golf club performance

Abstract: PurposeThe purpose of this paper is to examine the extent to which strategic marketing planning is carried out by Australasian golf clubs and the impact such planning has upon their business performance.Design/methodology/approachA research methodology borrowed from the “for profit” sector is applied. In total, ten basic strategic marketing practices, each with its own hypothesis, are investigated through a web‐based survey of secretaries/managers of 180 Australian and New Zealand golf clubs.FindingsAnalysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…After investigating 10 basic strategic marketing practices and their relationships with competitive business performance, those authors discovered that although most golf courses had adopted strategic marketing, higher-performing ones had placed far greater emphasis on each of the 10 practices [45]. As other authors have shown, strategic marketing planning typically consists of five steps: conducting a comprehensive strategic situation analysis, developing marketing objectives, formulating a marketing strategy, organising for marketing and using strategic control procedures [46]. In somewhat related research, Pereira et al [47] analysed promotional texts on golf-related websites as sources for identifying brand personality traits.…”
Section: Golf and The Tourist Industrymentioning
confidence: 99%
“…After investigating 10 basic strategic marketing practices and their relationships with competitive business performance, those authors discovered that although most golf courses had adopted strategic marketing, higher-performing ones had placed far greater emphasis on each of the 10 practices [45]. As other authors have shown, strategic marketing planning typically consists of five steps: conducting a comprehensive strategic situation analysis, developing marketing objectives, formulating a marketing strategy, organising for marketing and using strategic control procedures [46]. In somewhat related research, Pereira et al [47] analysed promotional texts on golf-related websites as sources for identifying brand personality traits.…”
Section: Golf and The Tourist Industrymentioning
confidence: 99%
“…Similarly to marketing plan, Garland, Brooksbank and Werder (2011) addresses the strategic marketing as a tool that "can be defined as an ongoing, organisation-wide and customer-led planning approach that facilitates optimal organisational responses to the fast changing and increasingly volatile modern business environment".…”
Section: Introductionmentioning
confidence: 99%
“…Additional topics include examinations of the effect of service quality and sportscape factors (Hill & Green, 2012;Lee, Kim, Ko, & Sagas, 2011), golf spectator experiences (Lambrecht, Kaefer, & Ramenofsky (2009), golf marketing (Brooksbank, Garland, & Werder, 2012;Garland, Brooksbank, & Werber, 2011), course tee time management (Haywood-Farmer, Sharman, & Weinbrecht, 1988), human resource management (Husin, Chelladurai, & Musa, 2012), golf course impacts on residential property values (Nicholls & Crompton, 2007), international trade of golf equipment (Andreff & Andreff, 2009), PGA Tour players' decisions to enter specific tournaments (Shmanske, 2009), and finally, designing, building, operating, and maintaining courses (Bartlett & James, 2011;Jackson, et al, 2011;Wheeler & Nauright, 2006). Wheeler and Nauright (2006) noted that "more people have become less tolerant of the impact that [golf] courses have" (p. 428) including the use of pesticides, water runoff, tree clearing, animal displacement, and health concerns related to golf courses.…”
mentioning
confidence: 99%